Hidden in plain sight: the overlooked establishment of the diamond lizardfish Synodus synodus (Linnaeus, 1758) in the Mediterranean Sea - DI FRANCO, ANTONIO; SOMMA, EMANUELE; DI LORENZO, MANFREDI; KOUTOULAKIS, YANNIS; FURUHASHI, RYUSEI; GIAKOUMI, SYLVAINE (Mediterranean Marine Science, 2026)
The Mediterranean Sea is a global hotspot for marine bioinvasions, with both alien and neo-native species reshaping its biodiversity. Among fishes, the diamond lizardfish Synodus synodus, a subtropical Atlantic taxon, has long been considered rare in the Mediterranean basin, with sporadic and questionable records. Here, we provide the first evidence of established S. synodus populations in the Mediterranean Sea, based on 34 individuals recorded across 18 sites in the Cyclades, Crete (Greece), and Linosa island (Italy). Most individuals were large, suggesting established populations. These findings indicate that S. synodus is more widespread than previously assumed, likely facilitated by ongoing seawater warming and ecological opportunities. Its unnoticed establishment highlights both the ecological relevance of neo-native fishes and the persistent challenges of detecting novel populations, even for conspicuous species, in an era of rapid marine biota restructuring.